2014
DOI: 10.1038/tp.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Grand-paternal age and the development of autism-like symptoms in mice progeny

Abstract: Advanced paternal age (APA) contributes to the risk of autism spectrum disorders (ASDs) in children. In this study, we used a mouse model to investigate the effects of APA on behavioral features related to autistic syndromes (that is, social deficits, communication impairments and stereotypic/repetitive behaviors). We also examined whether such effects are transmitted across generations. To do this, males aged 15 months (APA) and 4 months (control) were bred with 4-month-old females, and the resulting offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 61 publications
9
39
0
Order By: Relevance
“…A smaller study found no evidence of a grandpaternal age-effect on ASD, but did find a maternal grandmother age-effect [91]. A recent animal study has reported that both the offspring and the second-generation offspring from older sires had altered ultrasound vocalization, as well as altered sociability, grooming, and anxiety-related behaviors [92]. Although the epidemiologic evidence is inconsistent, the possibility of phenotypically silent effects in offspring later manifested in grandchildren has substantial implications for the future societal burden of ASD and is well worth investigating.…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 99%
“…A smaller study found no evidence of a grandpaternal age-effect on ASD, but did find a maternal grandmother age-effect [91]. A recent animal study has reported that both the offspring and the second-generation offspring from older sires had altered ultrasound vocalization, as well as altered sociability, grooming, and anxiety-related behaviors [92]. Although the epidemiologic evidence is inconsistent, the possibility of phenotypically silent effects in offspring later manifested in grandchildren has substantial implications for the future societal burden of ASD and is well worth investigating.…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 99%
“…Paternal aging has recently received a particular attention as an important factor that contributes to the etiopathogenesis of many psychiatric disorders, including ASD and ADHD [4045]. The detrimental effects of paternal aging has been largely investigated in rodents; for example, offspring derived from aged father showed learning deficits, impaired social behavior, hyperactivity and anxiety traits [4648]. However, the interplay between paternal aging and a genetic risk is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While epigenetic inheritance of methylation patterns are often paternally derived, 16 other types of epigenetic inheritance may be maternally derived, including non-coding RNAs. [18][19][20][21][22][23] One explanation for this relationship is that genes encoding proteins that form synapses in the brain are usually longer genes 24 and therefore have an increased probability of acquiring a mutation by chance with aging. [18][19][20][21][22][23] One explanation for this relationship is that genes encoding proteins that form synapses in the brain are usually longer genes 24 and therefore have an increased probability of acquiring a mutation by chance with aging.…”
mentioning
confidence: 99%